Survival of children and adolescents with intellectual disability following gastrostomy insertion - Wong, K.; Glasson, E.J.; Jacoby, P.; Srasuebkul, P.; Forbes, D.; Ravikumara, M.; Wilson, A.; Bourke, J.; Trollor, J.; Leonard, H.; Nagarajan, L.; Downs, Jennepher (WILEY, 2020)
Background: Positive health outcomes have been observed following gastrostomy insertion in children with intellectual disability, which is being increasingly used at younger ages to improve nutritional intake. This study investigated the effect of gastrostomy insertion on survival of children with severe intellectual disability.